Dental pulp regeneration via cell homing. (7th November 2017) - Eramo, S.; Natali, A.; Pinna, R.; Milia, E.
Abstract: The typical treatment for irreversibly inflamed/necrotic pulp tissue is root canal treatment. As an alternative approach, regenerative endodontics aims to regenerate dental pulp‐like tissues using two possible strategies: cell transplantation and cell homing. The former requires exogenously transplanted stem cells, complex procedures and high costs; the latter employs the host's endogenous cells to achieve tissue repair/regeneration, which is more clinically translatable. This systematic review examines cell homing for dental pulp regeneration, selecting articles on in vitro experiments, in vivo ectopic transplantation models and in situ pulp revascularization. MEDLINE/PubMed and Scopus databases were electronically searched for articles without limits in publication date. Two reviewers independently screened and included papers according to the predefined selection criteria. The electronic searches identified 46 studies. After title, abstract and full‐text examination, 10 articles met the inclusion criteria. In vitro data highlighted that multiple cytokines have the capacity to induce migration, proliferation and differentiation of dental pulp stem/progenitor cells. The majority of the in vivo studies obtained regenerated connective pulp‐like tissues with neovascularization. In some cases, the samples showed new innervation and new dentine deposition. The in situ pulp revascularization regenerated intracanal pulp‐like tissues with neovascularization, innervation and dentine formation. Cell homing strategies for pulp regeneration need further understanding and improvement if they are to become a reliable and effective approach in endodontics. Nevertheless, cell homing currently represents the most clinically viable pathway for dental pulp regeneration.